Existence of Solutions to Elliptic Equation with Exponential Nonlinearities and Singular Term (Journal of Partial Differential Equations, 2019)
In this paper, we consider an elliptic equation with exponential nonlinearitiesand singular term. By constructing the corresponding variational framework, andusing a Singular Trudinger-Moser inequality due to Li, Mountain-pass theorem andthe Ekeland’s variational principle, we get a nontrivial positive weak solution.